2012
DOI: 10.1002/aehe.20005
|View full text |Cite
|
Sign up to set email alerts
|

Table of Contents

Abstract: Executive Summary Foreword Acknowledgments The Case for a Comprehensive Model of College Readiness The Complexity of College Readiness Quasi‐Ecological Approaches to College Readiness The Next Generation of College Readiness Research Method and Organization The Human Ecology Framework Principles of Development in Ecological Systems Environmental Contexts Environmental Interactions: A Fully Ecological Model Individual: The Attributes of College Readiness Resource Characteristics Force Characteristics Demand Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…Person-environment theory: where and how doctoral education takes place in doctoral programs, as it encompasses the interacting forces of ideology and culture, social and organizational structure, time, and individual agency (Arnold et al, 2012). Environments are interactive and include macro-, exo-, meso-, and microsystems.…”
mentioning
confidence: 99%
“…Person-environment theory: where and how doctoral education takes place in doctoral programs, as it encompasses the interacting forces of ideology and culture, social and organizational structure, time, and individual agency (Arnold et al, 2012). Environments are interactive and include macro-, exo-, meso-, and microsystems.…”
mentioning
confidence: 99%
“…Both of these concepts have moved beyond a limited focus on academic preparation, only. Arnold, Lu, and Armstrong's (2012) ecological model of college readiness has been the most complex and comprehensive model proposed to date. By combining a number of research studies and models of readiness, Arnold et al's model has identified five key aspects of academic preparation: college knowledge, self-efficacy, motivation, academic skills and discipline, and aspirations.…”
Section: Models Of College Readinessmentioning
confidence: 99%
“…Like Arnold et al (2012) a number of researchers have viewed college readiness as an interplay between the individual and collective efforts of multiple stakeholders (Baker et al, 2005;Yamamura, Martinez, & Saenz, 2010). Such views have, therefore, connoted a shared responsibility for the adequate preparation of school-aged youth for college.…”
Section: Models Of College Readinessmentioning
confidence: 99%